2021
DOI: 10.3389/fphar.2021.773185
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Pharmacology, Safety, and Clinical Applications of Yunnan Baiyao, a Traditional Chinese Medicine Formula

Abstract: Ethnopharmacology relevance: Yunnan Baiyao (YNBY), a traditional Chinese medicine formulae, has some significant properties including activating blood circulation to dissipate blood stasis (Huo-Xue-Hua-Yu), eliminating swelling and alleviating pain (Xiao-Zhong-Zhi-Tong), and eliminating necrotic tissues and promoting granulation (Qu-Fu-Sheng-Ji).Aim of this study: This paper intends to provide a comprehensive and critical analysis of studies on YNBY, proposing new possible therapeutic directions of this formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Notoginseng Radix et Rhizoma [Araliaceae; Panax notoginseng (Burkill) F.H.Chen] has been used for hundreds of years in traumatic injuries and various kinds of bleeding ( Ren et al, 2020 ). Notoginseng Radix et Rhizoma is an important component of Yunnan Baiyao, and Yunnan Baiyao is a famous commercial medicinal product in China, which is widely used for wounds ( Yao et al, 2021 ). Saponins isolated from Notoginseng Radix et Rhizoma are the active components.…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…Notoginseng Radix et Rhizoma [Araliaceae; Panax notoginseng (Burkill) F.H.Chen] has been used for hundreds of years in traumatic injuries and various kinds of bleeding ( Ren et al, 2020 ). Notoginseng Radix et Rhizoma is an important component of Yunnan Baiyao, and Yunnan Baiyao is a famous commercial medicinal product in China, which is widely used for wounds ( Yao et al, 2021 ). Saponins isolated from Notoginseng Radix et Rhizoma are the active components.…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…Pharmacological studies have shown that Rhizoma Paridis has significant antitumor, hemostatic, antiinfection, and antioxidant activities ( Zhao et al, 2009 ; Liu et al, 2012b ). Rhizoma Paridis is the main ingredient in well-known TCPMs including Yunnan Baiyao, Gongxuening capsule, and Baibaodan that are mainly used for promoting blood circulation, removing blood stasis, heat-clearing, detoxifying, and regulating menstruation, according to TCM theory ( Liu et al, 2009 ; Yao et al, 2021 ). Moreover, as a traditional anticancer TCM, the active ingredients of Rhizoma Paridis have been widely studied as potential new anticancer drugs.…”
Section: Methods and Strategiesmentioning
confidence: 99%
“…At present, YNBY has been observed to cause various effects such as wound-healing, procoagulant, analgesic, anti-inflammatory, antitumour, antibacterial, and other effects. 5 , 6 Current investigations have indicated that YNBY exhibits antiarthritic properties through the reduction of the T helper 17 (Th17)/regulatory T cells (Tregs) ratio, regulation of cytokine balance, and repression of OC activity. 7 …”
Section: Introductionmentioning
confidence: 99%